Pemanfaatan Kecerdasan Artifisial Generatif dalam Proses Desain - Taufik Achirjun Ibrahim; Achmad Syarief; Yannes Martinus Pasaribu (Institut Seni Indonesia Yogyakarta, 2026)
Generative AI (GAI) is reshaping how designers work, yet little is known about human-AI collaboration in design firms outside developed countries. This study explores how GAI changes ideation practices and designers' roles, proposing a human-centred leadership framework for managing that collaboration. Existing research tends to focus narrowly on either AI's technical capabilities or broad philosophical debate, leaving a gap between GAI's productivity gains and its risks to originality and creative identity. Using mixed-methods action research built around Design Thinking, 15 multidisciplinary designers at an Indonesian design firm involved on a real banking project. Interviews, observations, and reflective journals were triangulated with perception surveys after each mode. Designers reported ideation speeding up roughly tenfold versus manual work, though results varied widely between individuals. Everyone encountered contextually inconsistent AI outputs, making human revision a permanent workflow step. Notably, no participant could verify the accuracy of outputs generated through AI-to-AI interactions—a phenomenon the study terms